Constructing Price Indexes across Space and Time: The Case of the European Union - Hill, Robert J (American Economic Review, 2004)
This paper considers the problem of how to construct and reconcile price indexes across space and time. A general taxonomy of panel price index methods, containing four broad classes, is proposed, along with five criteria for discriminating between them. Methods from each of the four classes are then used to compute spatial and temporal price indexes for the 15 countries of the European Union (EU) over the period 1995–2000. Using these panel price indexes, I test whether or not price levels and relative prices converged across the EU over this period.